Axiological Dimension of Public Servants: Historical Heri-tage and the Demands of Modernity - Pashkin, A. M. (Psychological Prospects Journal, 2011)
The article deals with a theoretical conside-ration of the phenomenon of organizational values in the context of the activities of public service, analysis of the historical background of its formation and characte-rization of the potential destructive impact of the mismatch of individual and organizational value systems. Suggesting measures to avoid axiological dissonance, as well as an algorithm empirical study of this phenomenon.
Keywords: values public administration laws civil service the organizational value system